PENGARUH METODE KOOPERATIF JIGSAW TERHADAP PRESTASI BELAJAR MATA PELAJARAN IPS PADA SISWA KELAS III - Sari, Maya Kartika (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
This study aims to determine the effect of the use of cooperative learning of jigsaw method in social studies on student achievement of class III SD Pakualaman Bantul and SD Gandok Islamiyah in 2014/2015 school year. This research design uses quantitative research methods. Collecting data in this study uses the test method. The used test methods in this research are the pre-test and post-test given to the experimental group and the control group. While the data analysis is a statistical method t test (t-test). The results of data analysis t test (t-test) obtained value = 3.34. At the significance level (α) = 0.05 and with db = 38 obtained value = 1.6859. So that is 3.34 ≥ 1.6859, therefore Ho is rejected H1 accepted. The conclusion of this study is that there is an effect on the use of cooperative learning of jigsaw model in social studies on student achievement of class III SD Islamiyah Pakualaman at school year 2014/2015. Keywords: Cooperative Model Jigsaw Type, Learning Achievement